BUXORO CHITTAGI PARUS BOCHARENSIS BIOLOGIYASI VA EKOLOGIYASIGA OID MATERIALLAR - Matekova G.A., Matekova G.A.; Bekniyazova D.B., Bekniyazova D.B.; Abdikarimova M.K, Abdikarimova M.K; Jumabayeva A.K., Jumabayeva A.K.; Arzibayev D.F., Arzibayev D.F.; Matekova T.A., Matekova T.A. (Actual problems and prospects of the study of the fauna, 2024)
The scientific work presents the materials related to the biology and ecology of the Bukhara chitta (Parus bocharensis) in the conditions of the Amudarya river flow are presented on scientific grounds.